Proceedings DCC '97. Data Compression Conference
DOI: 10.1109/dcc.1997.582009
|View full text |Cite
|
Sign up to set email alerts
|

Block sorting and compression

Abstract: The Block Sorting Lossless Data Compression Algorithm (BSLDCA) described by Burrows and Wheeler [3] has received considerable attention. It achieves as good compression rates as context-based methods, such as PPM, but at execution speeds closer to Ziv-Lempel techniques [5]. This paper, describes the Lexical Permutation Sorting Algorithm (LPSA), its theoretical basis, and delineates its relationship to BSLDCA. In particular we describe how BSLDCA can be reduced to LPSA and show how LPSA could give better result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 4 publications
1
22
0
3
Order By: Relevance
“…Stable sorting reserves the order of the same symbols. If we represent the sorted version of y [1, n] by z[1, n], we have Then, we write for the symbol y i if it appears as the jth symbol z j in z[1, n] [6]. In the present example, we have S1 5, S2 6, S3 7, and so on.…”
Section: Block-sorting Data Compressionmentioning
confidence: 94%
“…Stable sorting reserves the order of the same symbols. If we represent the sorted version of y [1, n] by z[1, n], we have Then, we write for the symbol y i if it appears as the jth symbol z j in z[1, n] [6]. In the present example, we have S1 5, S2 6, S3 7, and so on.…”
Section: Block-sorting Data Compressionmentioning
confidence: 94%
“…These claims are supported by experience. Arnavut and Magliveras 14 have shown that the Burrows-Wheeler Transform is but one of a group of permutations, and that it may be possible to select a permutation group with better compression and accompany the compressed data with an ordinal group index or a coding of the permutation itself.…”
Section: Block Sorting or Burrows-wheeler Transformmentioning
confidence: 99%
“…Itoh und Tanaka entwickelten 1999 ein neues Verfahren -das sogenannte "Two Stage Suffix Sort" - [12], welches von Kao im Rahmen einer Dissertation aufgegriffen und speziell für Folgen von sich wiederholenden Zeichen optimiert wurde [13].Auch die der Burrows-WheelerTransformation nachgeordneten Stufen sind Gegenstand zahlreicher Untersuchungen gewesen. Hierzu zählen insbesondere die Erweiterungen von Arnavut and Magliveras aus dem Jahre 1997 [2], von Balkenhol und Shtarkov aus dem Jahre 1999 [4], von Deorowicz aus dem Jahre 2000 [8] und 2002 [9] sowie von Abel aus dem Jahre 2003 [1].…”
Section: Einführungunclassified
“…Hierbei besteht die GST aus zwei Unterstufen, die in Abb. 2 hand der Zeichenfolge ABRAKADABRAABRAKADABRAAB-RAKADABRA verdeutlicht. Zur besserenÜbersicht werden die Ein-und Ausgabedaten der Stufen in Abb.…”
Section: Der Aufbau Der Erweiterten Varianteunclassified